New publication: Marlene Laruelle. Russia’s Arctic Strategies and the Future of the Far North. New York. 2013. 251 p. - O. A. Anisimov (Лëд и снег)
New publication: Marlene Laruelle. Russia’s Arctic Strategies and the Future of the Far North. New York. 2013. 251 p.